Historical evolution of cataloging over time - Rodriguez Calvo, Desiree (2024)
The article examines the evolution of cataloging from ancient Sumerian tablets to current standards in the contemporary digital age. The relevance of structuring and classifying knowledge is highlighted in order to expide access and retrieval of information optimally. The milestones and key figures that have shaped the organization of knowledge over the centuries are analyzed, as well as the theoretical and practical currents that have influenced the development of cataloging regulations. The continuous evolution of cataloging procedures is highlighted, from the first book inventories to the adoption of contemporary standards such as RDA and conceptual models such as FRBR and FRAD. Likewise, the incorporation of technological advances such as the MARC 21 format and the implementation of linked data are mentioned, which have expanded search and discovery capabilities. The article emphasizes the importance of standardization and the processing of information in today's digital world.